(untitled) (Gestión y Gerencia, 2024)
This essay analyzes the historical evolution and current state of the labor competencies required for digital transformation in the public sector. Through a literature review, key stages, approaches, and projects that have shaped the concept of labor competency were identified. The results reveal a constant evolution of competencies, driven primarily by technological changes and new societal demands. Integrating knowledge, skills, and attitudes to adapt to a dynamic and efficient work environment is highlighted. However, the essay also evidences the need to address outstanding challenges in the implementation and measurement of competencies.